2003
DOI: 10.1002/arch.10112
|View full text |Cite
|
Sign up to set email alerts
|

Chloride channels as tools for developing selective insecticides

Abstract: Ligand-gated chloride channels underlie inhibition in excitable membranes and are proven target sites for insecticides. The gamma-aminobutyric acid (GABA(1)) receptor/chloride ionophore complex is the primary site of action for a number of currently used insecticides, such as lindane, endosulfan, and fipronil. These compounds act as antagonists by stabilizing nonconducting conformations of the chloride channel. Blockage of the GABA-gated chloride channel reduces neuronal inhibition, which leads to hyperexcitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
1
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(132 citation statements)
references
References 58 publications
2
123
1
6
Order By: Relevance
“…For example, nAChRs are targets of neonicotinoids, which have been the fastest-growing class of insecticides in modern crop protection (Jeschke and Nauen, 2008). In addition, GABA receptors, GluCls and HisCls are targets of fipronil and avermectins (Iovchev et al, 2002;Bloomquist, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, nAChRs are targets of neonicotinoids, which have been the fastest-growing class of insecticides in modern crop protection (Jeschke and Nauen, 2008). In addition, GABA receptors, GluCls and HisCls are targets of fipronil and avermectins (Iovchev et al, 2002;Bloomquist, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, although we found that cadherin is not involved in P. xylostella Bt Cry1Ac resistance (52), we revealed that down-regulation of ALP, ABCC2, ABCC3, and a novel ABCG1 (white) genes are all associated with Cry1Ac resistance in P. xylostella (77,78). Acetylcholinesterase (AChE), as a hydrolase, which hydrolyzes the neurotransmitter acetylcholine was the target of organophosphorus insecticide; chloride channel was studied as insecticidal target (79). Ryanodine receptors (RyRs) are the major cellular mediator of calciuminduced calcium release in animal cells.…”
Section: Proteogenomics Of P Xylostella Larval Midgutmentioning
confidence: 99%
“…Fipronil's insecticidal activity is mediated primarily through its actions as a non-competitive antagonist of GABR. In this regard, fipronil was initially developed as an insecticide because of its higher selectivity for insect forms of GABR relative to mammalian GABR (Bloomquist 2003). However results from recent studies indicate that fipronil, like endosulfan and lindane, is indeed a high affinity noncompetitive antagonist for the mammalian β 3 -homopentameric GABR (GABRβ 3 ) (Chen et al,2006;Sammelson et al, 2004).…”
Section: Chemicals That Interfere With Gaba Neurotransmissionmentioning
confidence: 99%